The effects of low electromagnetic field and lead acetate combination on some hemato-biochemical and immunotoxicological parameters in mice - Nabela Imam El-sharkawy; Mohamed Abd El-azim Hashem (Turkish Journal of Hematology, 2009)
Objective: The present study was carried out to investigate the potential effects of extremely low-frequency electromagnetic fields (ELF-EMF) and lead acetate on some hemato-biochemical, immune and pathologic variables in mice. Material and Methods: A total of 90 female mice were equally divided into six groups. (Gp. 1) kept as control, (Gp. 2) exposed to EMF of 2 millitesla (mT) intensity and 50 Hz frequency (4h/day) for 30 days, (Gps. 3 and 4) were administered lead acetate orally at doses 1 and 5 mg/kg BW, respectively for 30 days. The last 2 groups (5, 6) were exposed to EMF- lead combination for the same period. Results: EMF exposure induced a significant increase in RBCs (p<0.001), WBCs (p<0.01) and platelets (p<0.001) counts, compared to control. However, anemia and leukopenia were recorded with oral administration of Pb acetate. The phagocytosis % and phagocytic index were significantly (p<0.05) increased in mice exposed to EMF for 30 days, but decreased (p<0.01) in the animals given the highest dose of lead. Comparing to unexposed mice, significant variation in biochemical parameters (glucose, enzymes, and protein profiles) were noticed. Combined lead and EMF treatments had antagonizing effect on some previous parameters, whereas mice given the highest dose of lead with EMF aggravated hemato-biochemical and pathological findings. Conclusion: We concluded that combined exposure to ELF-EMF and Pb acetate produced significant changes in the hemato-biochemical and immune parameters which were both real and inconsistent.